Biparental care is more than the sum of its parts: experimental evidence for synergistic effects on offspring fitness. Issue 1884 (1st August 2018) - Pilakouta, Natalie; Hanlon, Elizabeth J. H.; Smiseth, Per T.
Abstract : Despite an extensive body of theoretical and empirical literature on biparental cooperation, it is still unclear whether offspring fare equally, better or worse when receiving care by two parents versus a single parent. Some models predict that parents should withhold the amount of care they provide due to sexual conflict, thereby shifting as much of the workload as possible to their partner. This conflict should lead to offspring faring worse with two parents. Yet, other models predict that when parents care for their offspring together, their individual contributions can have synergistic (more than additive) effects on offspring fitness. Under this scenario, biparental cooperation should lead to offspring faring better with two parents. We address this fundamental question using a unique experimental design where we compared offspring fitness when the two parents worked together (biparental treatment) and when they worked separately (uniparental treatment), while keeping constant the amount of resources and number of offspring per parent across treatments. This made it possible to directly compare the biparental treatment to the sum of the male and female contributions in the uniparental treatment. Our main finding was that offspring grew larger and were more likely to survive to adulthood when reared by both parents than a single parent. This is the first empirical evidence for a synergistic effect of biparental cooperation on offspring fitness and could provide novel insights into the conditions favouring the evolution of biparental cooperation.